Mânûnjjâlînj Kâwûlâ Jûstî ‘Inda Râdîn Njâbîhî Rânjjâ Wârsîtû fî Risâlatî Wîrîd Hidâyat Jâtî fî Ta’lîmi Kîjâwîn (Kîbâtînân) fî Dhowi al-Tawhid al-Islâmiy. - Kholid Karomi; Dyah Ayu Rejekiningtyas (Departement of Comparative Study of Religions, 2020)
Manunggaling Kawula Gusti is the science of the high level of the Javanese to acquire the degree of perfection. In Kejawen, it is central to his teachings. However, in its history, the concept is not apart of the debate. It is said that Manunggaling Kawula Gusti is based to the teachings of the monistic and pantheistic. This teaching spreaded by Ranggawarsita, and write the complete fiber that discuss about Manunggaling Kawula Gusti. The fiber is Serat Wirid Hidayat Jati. He is a figure that represents a concept that is raised by the process of acculturation the two great major, the Islamic tradition and Kejawen tradition. Then, the pattern of Ranggawarsita thought influenced by the two traditions. This leads to not represent one of the tradition as a whole. The discussion aims to uncover Manunggaling Kawula Gusti according to Ranggawarsita in Serat Wirid Hidayat Jati, and the views of Islamic Monotheism against the doctrine. At the end of this discussion, will explain that the concept of Manunggaling Kawula Gusti teaches that the God is transcend with human, but His names and natures are close with human. That the meant of Manunggaling Kawula Gusti is Lord and servant is unity of creativity, taste and intention. Manunggaling Kawula Gusti may not be viewed as the teachings that deviate from monotheism, and instead, it is a form of the highest expression of the tawhid. This docrine teaches that there is no manifestation of the essential in addition to form of God.